Lesional Incidence in a Women's Professional Basketball Team during a Complete Season - Olga Blanco; Javier Fernandez-Rio (Journal of Novel Physiotherapy and Physical Rehabilitation - Peertechz Publications, 2015)
Background: The purpose of this study was to assess the lesional incidence of a professional basketball team during a complete season, noting the type of injuries that take place and their recuperation times, in parallel with the recovery treatments used.  Method: 11 players of a Spanish division-II basketball players (23.45 ± 5.44 years) and their athletic trainer agreed to participate. All injuries occurred during the 2013-14 Spanish division-II women's basketball season and their treatment were recorded and classified. Conclusions: The injuries that occurred during the 2013-14 season, to a large extent, were mild with a fast recovery time; being the musculoskeletal disorders of the lower limb and the lower back the most common ones. The majority of them were produced during practice, not competition.